Analysis Of The Effectiveness Of Pmse Vat Collection Based On The Tax Directorate's Instructions In Increasing Tax Revenue At The Primary Tax Offce Of West Bekasi - Ida Seran, Willigis (Indonesian Scientific Publication, 2023)
Through law Number 2 of 2020, the Indonesian government began to impose taxes on Trading Transactions Through the Electronic System (PMSE). The phenomenon behind this research is the many obstacles that caused the realization of PMSE VAT revenue in certain years to fail in meeting the targets set by the government; 99.13% in 2019 and 85.17% in 2020. Only in 2021 the PMSE VAT revenue exceeded the target, i.e. 101.39%. Meanwhile, the number of registered Taxable Entrepreneurs (PKP) continues to increase every year. This study was conducted to analyze the effectiveness of PMSE VAT collection based on the instructions of the Directorate of Taxes in increasing tax revenue at the Primary Tax Offce of West Bekasi in 2019-2021. In this study the author used Duncan's theory of effectiveness (in Sterrs 1985: 53) which states that to assess the effectiveness of a tax, certain criteria are required, such as realization of goals, integration, and adaptation. The approach used in this research is a qualitative approach with a descriptive method. Data was collected through observation, documentation and interviews. The results of this study indicate that PMSE VAT collection has been going well but not yet fully effective because in certain years it did not reach the target due to several obstacles experienced by the Primary Tax Offce of West Bekasi, including inadequate infrastructure, and low awareness and knowledge of PMSE VAT.